Integration of Quality Measures in Project Control System for Construction Organizations - Abdullah, Abdul Rahman Ramakrishna (2004)
Current project control system is not capable of initiating effective control actions to remedy performance shortfalls and overcome the occurrences of project overruns. The weakness in current system is that it does not evaluate quality performance together with schedule and cost performances of construction projects to initiate control actions. The research develops a method for deriving quality measure using material usage data and integrates the measure in current project control system to determine if project control is enhanced with the integration. Current project control system integrated with quality measure is applied in several ongoing construction projects and it is found to result significant improvement in the performance of the projects. The combined schedule, cost and quality performances in v projects initiated with control actions improved by 54%, 72% and 3% respectively. The organization’s mean value for schedule, cost and quality performances also improved by 22%, 9.6% and 3% respectively and the standard deviation for schedule and quality performances reduced by 38% and 62% respectively. The deviation for cost performance however increased by 3% due to an abrupt leap in the cost performance of a single project, which was not subjected to control actions. While performances in projects subjected to control actions improved significantly projects that were not subjected to similar control had schedule and cost performances deteriorated by 2.64% and 8% respectively. The substantial improvement achieved in projects subjected to control actions from using this upgraded control system validates the research hypothesis that integration of quality measure enhances its effectiveness in controlling project performance.